Reduction of Fuel Consumption Normal in Regenerative Furnaces ith Moving and Blown-Through Layer while Producing Lime from CaCO3 - V. А. Sednin; A. P. Nesenchuk; A. G. Kozhevnikov; I. V. Melnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
Formulation of the problem concerning optimal numerical modeling of CaCO3 roasting with the purpose to obtain highly qualitative final product CaO for metallurgical electric arc furnaces is given in the paper.Modeling results in reduction of CaCO3 overheating at the stage of roasting. The paper proposes a substitution of the processes taking place at all stages by a large scale process of CO2 desorption from CaCO3 with CaO formation.